2017
DOI: 10.1128/aac.02446-16
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacodynamics of Finafloxacin, Ciprofloxacin, and Levofloxacin in Serum and Urine against TEM- and SHV-Type Extended-Spectrum-β-Lactamase-Producing Enterobacteriaceae Isolates from Patients with Urinary Tract Infections

Abstract: The pharmacodynamics of finafloxacin, ciprofloxacin, and levofloxacin against extended-spectrum-β-lactamase (ESBL)-producing Enterobacteriaceae isolates were compared. Since quinolones lose activity in acidic media, and particularly in urine, their activities were tested in parallel under conventional conditions and in acidic artificial urine. For this purpose, TEM- and SHV-type ESBL-producing Escherichia coli and Klebsiella pneumoniae strains and their wild-type counterparts were exposed in a modified Grasso … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
13
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 72 publications
0
13
0
2
Order By: Relevance
“…All researchers are clinical doctors and receive standardized training for the diagnostic interview before the start of the trial. Levofloxacin tablets are licensed for UTI with proven curative effect and safety [32]. Therefore, levofloxacin have been selected as the active control medicine.…”
Section: Interventionsmentioning
confidence: 99%
“…All researchers are clinical doctors and receive standardized training for the diagnostic interview before the start of the trial. Levofloxacin tablets are licensed for UTI with proven curative effect and safety [32]. Therefore, levofloxacin have been selected as the active control medicine.…”
Section: Interventionsmentioning
confidence: 99%
“…All researchers are clinical doctors and receive standardized training for the diagnostic interview before the start of the trial. Levofloxacin tablets are licensed for UTI with proven curative effect and safety [32].Therefore, levofloxacin had been selected as the active control medicine. Participants in the experimental group will receive SJT plus LT placebo orally four times a day for 7 days.…”
Section: Interventionsmentioning
confidence: 99%
“…The photocatalytic degradation of ciprofloxacin and levofloxacin (isoelectric points (zwitterion): 7.4 and 6.8, respectively) [18], applying the ZnO/Au composite nanowires as catalysts, was studied using a continuous flow reactor. For comparative studies, neat ZnO nanotubes and Degussa P25 (TiO2 based photocatalyst) were used.…”
Section: Photocatalytic Degradation Of Negatively Charged Antibioticsmentioning
confidence: 99%
“…For ciprofloxacin the isoelectric point of the zwitterion is at a pH value of 7.4. [18] Thus, a catalyst bearing a positive surface charge at a pH of 8 is advantageous, as this will enhance the electrostatic interactions between antibiotic and catalyst. Previous studies showed that in contrast to Degussa P25, a TiO2 catalyst with its point of zero charge (PZC) at a pH of 6.9, ZnO fulfils this requirement as its PZC is 9.2.…”
mentioning
confidence: 99%